Convergence and distortions: The Czech Republic, Hungary and Poland between 1996-2009 - István Kónya (Magyar Nemzeti Bank, 2011)
The paper interprets the growth and convergence experience of three Central-Eastern European economies (the Czech Republic, Hungary, and Poland) through the lens of the stochastic neoclassical growth model. It adapts the methodology of Business Cycle Accounting (Chari, Kehoe and McGrattan 2007) to economies on a transition path. The paper uses the method to uncover distortions (wedges) on the labor and capital markets, and then presents various comparisons and counterfactuals based on them. Results show that (i) capital and labor market distortions vary across the three economies, but they are well within the range of advanced economies; (ii) the Polish and Hungarian labor wedges are high, and the Czech labor wedge increases; (iii) the evolution of Hungarian wedges followed a different path than the evolution of Polish and Czech wedges, and (iv) realistic reductions in the capital and labor wedges would lead to significant output gains for Hungary and Poland.
Keywords: E13; O11; O47; 330; convergence; distortions; Central-Eastern Europe; business cycle accounting